Microfluidic rheometer based on hydrodynamic focusing - Nguyen, Nam-Trung (2012)
This paper reports the concept and the optimization of a microfluidic rheometer based on hydrodynamic focusing. In our microfluidic rheometer, a sample stream is sandwiched between two sheath streams. The width of the middle stream depends on the viscosity ratio and the flow rate ratio of the liquids involved. Fixing the flow rate ratio and using a known Newtonian liquid for the sheath streams, the viscosity and the shear stress of the sample stream can be determined by measuring its width and using a prediction algorithm that uses the known channel geometries, fluid properties, flow rates and the focused width as input parameters. The optimization reveals that a measurement channel with a high aspect ratio is more suitable for a sample liquid with viscosity higher than the reference value. For a sample liquid with viscosity of the same order of magnitude or lower than the reference, a low aspect ratio is more suitable. Furthermore, the measurement range and the relative error can be improved by adjusting the flow rate ratio between the core stream and the sheath stream. A microfluidic device was fabricated in polymethylmethacrylate (PMMA). Using this device, viscosities of deionized (DI) water and polyethylene oxide (PEO) solutions were measured and compared with results obtained from a commercial rheometer.